КОНЧИЛИК ЙЎНАЛИШИ ТАЛАБАЛАРИ КАСБИЙ ЛЕКСИК КОМПЕТЕНЦИЯСИНИ АХБОРОТ ТЕХНОЛОГИЯЛАРИ ЁРДАМИДА РИВОЖЛАНТИРИШ КОМПОНЕНТЛАРИНИНГ ТАВСИФИ - Сайдуллаева, Х.У. (SCIENCE and SOCIETY, 2022)
The scientific article explores the principles of selection of lexical material while teaching students foreign languages and important components of the effective use of information technology in the development of professional lexical competence.
Keywords: information technologies; professional lexical competence; visual method; the English language